Early Carboniferous coiled nautiloids from the Anti-Atlas (Morocco) - Korn, Dieter; Klug, Christian (European Journal of Taxonomy, 2023)
Viséan coiled nautiloids from North Africa are only poorly known. From the Mougoui Ayoun, Zrigat and Hamou-Rhanem formations of the eastern Anti-Atlas, we describe coiled nautiloids, which belong to the genera Rineceras, Stroboceras, Temnocheilus, Vestinautilus, Maccoyoceras, Endolobus, Epidomatoceras, Liroceras, Ephippioceras, and Solenochilus. The new species Temnocheilus imazighenorum sp. nov., Temnocheilus aubrechtovae sp. nov., Vestinautilus kesslerae sp. nov., Endolobus rota sp. nov., Epidomatoceras ebbighausenorum sp. nov., Liroceras vermis sp. nov., Liroceras karaouii sp. nov., Ephippioceras pygops sp. nov., Solenochilus lucynae sp. nov. and Solenochilus pohlei sp. nov. are described; six taxa are kept in open nomenclature. The assemblage is composed of the three superfamilies Trigonoceratoidea, Clydonautiloidea and Aipoceratoidea and shows a wide spectrum of conch morphologies, ranging from widely umbilicate compressed forms to involute compact forms, reflecting a broad ecological variation.